Effect of mall environment on consumer buying behavior in Melaka City / Nabila Ahmad - Ahmad, Nabila (Faculty of Business and Management, 2018)
This study was conducted in order to determine the effect of mall environment on consumer buying behavior in Melaka City. It investigated the preferences of mall consumers for the factor affecting their consumer buying behavior. The study used a survey questionnaire to gather information from the consumers by passing to the consumers individually to get an instant answer. The theoretical framework of this study was based on consumer behavior theories from various authors. For example, empirical evidence suggests that the success of shopping malls today lays in their ability to offer customers both consumer and social experiences under one roof (Dennis et al., 2002; Haytko and Baker, 2004) and these issues were discussed in the literature review. The findings of the study indicated that aesthetics is the most affecting factor for consumer buying behavior.